Identification of Hypermethylated Genes Associated with Cisplatin Resistance in Human Cancers - Chang, Xiaofei (2010)
Cisplatin is among the most widely used cytotoxic anti-cancer agents in solid tumors, however, the development of secondary resistance remains a major obstacle to clinical efficacy. Treatment-related DNA hypermethylation may play a role in creating drug resistant phenotypes by inactivating genes that are required for cytotoxicity. We applied a pharmacologic unmasking approach to detect hypermethylated genes whose inactivation contributes to cisplatin resistance. Utilizing three pairs of isogeneic, cisplatin-sensitive and -resistant cell lines derived from two parental cell lines (KB-3-1 and SCC25), we identified several hundred genes that were down-regulated in each resistant cell line and re-activated by the DNA methyltransferase inhibitor 5-Aza-2'-deoxycytidine (5-Aza-dC). Among them, 30 genes were common to ≥ 2 cell lines, and/or reported to be down-regulated in previous studies. Bisulfite sequencing confirmed that 14 genes were hypermethylated in resistant cell lines, but not in the sensitive parental cell lines. Six of 14 genes (SAT, C8orf4, LAMB3, TUBB, G0S2, MCAM) were cisplatin-inducible in sensitive, but not in resistant cell lines. siRNA knockdown of two genes, SAT and S100P, increased cell viability with cisplatin treatment in sensitive parental cell lines. S100P knockdown significantly decreased the S-phase fraction (SPF) of parental sensitive cell lines and slowed cell proliferation, which was associated with decreased sensitivity to cisplatin. Based on these findings, we conclude that DNA methylation is a frequent event in cells that are chronically exposed to cisplatin, and that methylation-induced gene silencing may play a role in the development of resistance to cytotoxic chemotherapeutic agents.